2004
DOI: 10.1002/ffj.1310
|View full text |Cite
|
Sign up to set email alerts
|

Micromorphology of trichomes and composition of essential oil of Teucrium capitatum

Abstract: The morphology and distribution of the glandular trichomes of Teucrium capitatum L., as well as the chemical composition of the essential oils, were studied. Important differences were found with regard to the major constituents of the essential oils of five populations of T. capitatum grown in Portugal. The oil isolated from one population was characterized by a high content of oxygenated monoterpenes (33.0%), isomenthone (7.7%) being the major constituent. Another oil from a population collected from the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 11 publications
3
27
0
1
Order By: Relevance
“…Based on studies carried out with Salvia blepharophylla, Brandegee ex Epling, Bisio et al [26] suggested two possible ways of release of secreted material: a) breakage of the cuticle; or b) via pores in the cuticle. As we could not observe any cuticle rupture on either peltate or capitate hairs, it seems plausible that the secretion release via cuticle pores may operate in the glandular hairs of our samples as T. capitatum L. [15]. After cuticule rupture in capitate hairs, the glandular head cell assumes a cup shape (Fig., 6 and 12), the type of hairs which has been reported for other species of Teucrium [3] [15] [16].…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Based on studies carried out with Salvia blepharophylla, Brandegee ex Epling, Bisio et al [26] suggested two possible ways of release of secreted material: a) breakage of the cuticle; or b) via pores in the cuticle. As we could not observe any cuticle rupture on either peltate or capitate hairs, it seems plausible that the secretion release via cuticle pores may operate in the glandular hairs of our samples as T. capitatum L. [15]. After cuticule rupture in capitate hairs, the glandular head cell assumes a cup shape (Fig., 6 and 12), the type of hairs which has been reported for other species of Teucrium [3] [15] [16].…”
mentioning
confidence: 80%
“…chamaedrys (16.7%), T. pestalozzae (13.8%), T. sandrasicum (27.9%), T. montanum (5.8%), and T. antitauricum (28.2%), and b-caryophyllene from T. chamaedrys subsp. lydium (19.7%), T. orientale (21.7%), T. pestalozzae (27.6%), and T. sandrasicum (9.1%) have been reported [15] [16] [23 -25].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…, T. orientale L. var. orientale (Javidnia & Miri, 2003;Yildirim et al, 2004), T. chamaedrys (Morteza-Semnani et al, 2005), T. capitatum L. (Antunes et al, 2004), T. libanitis Schreb. and T. turredanum Losa and Rivas Goday (Blazquez et al, 2003), T. divaricatum Heldr.…”
Section: Introductionmentioning
confidence: 99%
“…The abaxial lamina ( Fig. 2D) is covered with sessile glands [B1 and B2 types; or Types I and II according to the denomination proposed by Antunes & Sevinate-Pinto (1991), or capitate and peltate according to Antunes et al (2004)] and long glandular spreading hairs (slightly antrorse) on the veins [not referred to by Antunes & Sevinate-Pinto (1991) for T. scorodonia plants; also not included in the description given by Navarro & El Oualidi (1997) for any of the species of Teucrium section scorodonia; also not referred to by Servettaz, Pinetti & Bini Maleci (1994) for T. siculum]. These long glandular hairs are of types A1, A2, and A3.…”
Section: Resultsmentioning
confidence: 99%